Anâlise do discurso sob a perspectiva bibliométrica nos estudos de ciência da informação no Brasil - Castanha, Renata Cristina Gutierres [UNESP]; de Mello Lima, Larissa [UNESP]; Martínez-Ávila, Daniel [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this paper is to evaluate Discourse Analysis in the studies of Information Science in Brazil, from the perspective of the bibliometric analysis of its discursive communities that are the research front dealing with this topic and theoretical influences. More specifically, it seeks to analyze the bibliometric indicators of production, citation, and relations in order to identify the most productive authors, scientific collaboration of authors, institutions and journals that address this issue, as well as to reveal and analyze their theoretical influences, understanding the structures in which researchers and topics work in Information Science. A search was conducted on the BRAPCI database in November 2015 including the terms discourse analysis (without quotation marks), “discourse analysis” and “discourse analysis,” together with “Foucault,” in order to retrieve all articles referring to the French School of discourse analysis. The results and analysis of these indicators consist on an essential tool for understanding the behavior of scientific discourse communities that address the French School of discourse analysis in studies of Information Science in Brazil.
Discourse analysis from the bibliometric perspective in the studies on information science in Brazil
Keywords: Bibliographic coupling; Bibliometric analysis; Citation analysis; Co-citation analysis; French school of discourse analysis